2D and 3D biotin patterning by ultrafast lasers. (1st December 2008) - Dinca, V.; Catherine, J.; Mourka, A.; Georgiou, S.; Farsari, M.; Fotakis, C.
Bio-micro-array fabrication and biological molecules patterning has been the focus of much research in recent years, as they are envisaged to play an important part in genomic studies, drug discovery and screening, protein identification and scaffolding development for tissue engineering. A number of different approaches have been examined for fabricating patterned biological surfaces. Almost in all cases, patterning of biomolecules has been two-dimensional. We demonstrate both 2D and 3D biotin patterning using techniques which enable the construction of arbitrary two and three dimensional shapes, not restricted to array-based shapes. For the 2D printing, Laser Induced Forward Transfer (LIFT) is employed to deposit controlled and viable micro-patterns of biotin. The activity and the functionality of the transferred materials are shown. For the 3D printing, firstly micro-structures are made employing multi-photon polymerisation. Biotin is subsequently immobilised on the structures surface by excimer laser photo-activation of photobiotin and further incubated with fluorescent labelled streptavidin. The specificity of the binding is demonstrated. The methods allow not only prototyping but also direct device construction.